2022
DOI: 10.1155/2022/3097436
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy of Retroauricular Injection of Methylprednisolone Sodium Succinate in the Treatment of Sudden Deafness with Type 2 Diabetes

Abstract: Background. The etiology of sudden deafness is still unclear. In recent years, people’s life rhythm is getting faster and faster. Fatigue, environment, diet, psychology, and other factors have increased the morbidity rate of sudden deafness and improved the quality of life of patients. And work efficiency is greatly affected. Aims. A study to investigate the clinical efficacy of postauricular injection of methylprednisolone sodium succinate in the treatment of sudden deafness with type 2 diabetes. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In addition, there are various topical medication methods, such as tympanic injection, retroauricular injection, and sustained-release pumps. Retroauricular injection has widely used in the clinical management of sudden deafness (22). The dose of administration via intratympanic injection is limited due to the volume of the tympanic chamber.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are various topical medication methods, such as tympanic injection, retroauricular injection, and sustained-release pumps. Retroauricular injection has widely used in the clinical management of sudden deafness (22). The dose of administration via intratympanic injection is limited due to the volume of the tympanic chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Retroauricular injections are performed subperiosteally in the mastoid process or at the midpoint of the retroauricular groove, penetrating the periosteum posteriorly before advancing approximately 1mm downward and forward to the bony surface behind the external auditory canal [27]. Both retroauricular injections and IST share similarities in rapid onset and low systemic circulation volume.…”
Section: Retroauricular Steroid Injectionsmentioning
confidence: 99%
“…The specific mechanism of action for retroauricular injections remains unclear; it may enter the inner ear through various routes such as circulation, permeation, and cerebrospinal fluid [29], achieving shorter peak times in the sigmoid sinus and outer lymphatic fluid with a longer duration of action. While there's no significant difference in overall cure rates [16,17], retroauricular injections show a more significant improvement in low-frequency hearing loss [30]. Jing et al [31] found a significant improvement in low-frequency thresholds for patients with conventional treatments ineffective for more than 2 weeks with retroauricular methylprednisolone injections, possibly related to improving inner ear labyrinthine hydrops.…”
Section: Retroauricular Steroid Injectionsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%